Internalisasi Nilai Karakter Berbasis Ideologi Keagamaan di Lembaga PAUD Berafiliasi NU - Umam, Nasrul; Islamy, Aufrina Nur; Bariroh, Bariroh (FONDATIA, 2023)
Internalization of ideology-based character values in PAUD institutions affiliated with Nahdlatul Ulama is the main thing as well as being the spirit of education. Administrators in charge of central education are concerned about compiling rules for establishing moral principles. However, only as a blueprint without any follow-up or assessment to gauge its effectiveness. Based on this phenomena, this study seeks to understand how RA Diponegoro 71 Banjarparakan internalizes religious ideology-based character values. This study is a case study-style qualitative investigation. Data collected through observation, interviews, and documentation procedures along with the snowball sampling approach. Source triangulation is then used to verify the accuracy of the data. Through the processes of data reduction, data display, and data verification, data were evaluated. The study's findings are as follows: 1) Tawasuth (moderate), tasamuh (tolerance), tawazun (balanced), i'tidal (perpendicular), and amar ma'ruf nahi munkar (calling on goodness and preventing evil) are character values based on religious ideology in RA Diponegoro 7 Banjarparakan. 2) Internalization of character values is carried out through habituation and learning in class. Habituation occurs on a daily, weekly, and annual basis. As for the design, carrying out, and evaluating learning activities: 3) An sufficient curriculum and supportive parents help the internalization of ideology-based character ideals. The internalization of character values must take into account the variations in student characteristics.